Questions of shipping policy - Uwe Christiansen (Intereconomics, 1979)
The states of the Third World will reassert their many known demands for improved integration in the international economic exchanges at UNCTAD V to be held in Manila in May and add new ones to their list of requests. It is clear from the first discussion papers prepared for the conference by the UNCTAD Secretariat that the sea-borne traffic will receive more attention in this catalogue of demands in future.
Keywords: 330; Unctad V